The sixth day - Coulter, Catherine; Ellison, J. T. (New York : Gallery Books, 2018)
"When several major political figures die mysteriously, officials declare the deaths are from natural causes. Then the German Vice-Chancellor dies on the steps of 10 Downing Street, and a drone is spotted hovering over the scene. The truth becomes clear--these high-profile deaths are well-constructed assassinations, and the Covert Eyes team is tasked to investigate."-- Book jacket.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Intelligence officers -- Fiction; Thrillers (Fiction); Detective and mystery fiction